Etiology and outcome of acute recurrent pancreatitis and chronic pancreatitis. Issue 1 (6th May 2022) - Getsuwan, Songpon; Tanpowpong, Pornthep; Lertudomphonwanit, Chatmanee; Junhasavasdikul, Thitiporn; Tim‐Aroon, Thipwimol; Treepongkaruna, Suporn
Abstract: Background: Owing to the lack of data, we aimed to determine the etiology and outcome of acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) in children in Southeast Asia. Methods: This retrospective study was conducted at a university hospital in Bangkok, Thailand. We included patients aged <18 years who were diagnosed with pancreatitis from 2000 to 2021. Results: Among 155 patients with pancreatitis, 21 (13.5%) were diagnosed with either ARP ( n  = 7) or CP ( n  = 14). Clinical manifestations of CP included chronic abdominal pain ( n  = 10, 71.4%), steatorrhea ( n  = 8, 57.1%), and diabetes mellitus ( n  = 1, 7.1%). Positive radiological findings compatible with CP were detected from an abdominal ultrasound, computed tomography, magnetic resonance cholangiopancreatography in 70%, 90.9%, and 92.9% of patients, respectively. Genetic, metabolic, and pancreaticobiliary causes were the major causes of ARP/CP (23.8% each) and the etiologies were unidentified in one‐fifth of the patients. Patients with metabolic diseases who had AP were at‐risk of developing ARP (hazards ratio [HR], 4.7, 95% confidence interval [CI]: 1.5–13.9). Children with ARP or CP were younger than those with AP ( P  = 0.04). Approximately two‐thirds of patients with CP had growth faltering and they had more episodes of hospitalization due to acute attacks when compared to patients with ARP ( 4 [interquartile range [IQR], 3–6] vs. 3 [IQR, 2–3]; P  = 0.02). Conclusion: Genetic, metabolic, and pancreaticobiliary diseases were the common etiologies of ARP and CP among children living in a developing country in Southeast Asia. The burden of CP included malnutrition and frequent hospitalization. The findings emphasize the importance of an early etiological diagnosis and monitoring for pancreatic insufficiency in ARP/CP.